2007
DOI: 10.1007/s10620-007-9940-z
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Adenosine 5′-triphosphate does not Improve Survival in Rats with Acute Liver Failure

Abstract: These findings suggest that exogenous ATP does not improve and indeed at high doses may impair survival in rats with acute liver failure. Further studies involving a wider range of ATP doses and different routes and frequency of ATP administration are required to determine whether exogenous ATP has therapeutic value in the treatment of acute liver failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Moreover, it has been established that hepatocellular glycogen level is a potentially important and manageable factor in maintaining hepatocellular integrity and function by generating ATP [27][28][29]. Once glycogen is consumed, ATP depletion rapidly develops, leading to a series of events that eventually cause irreversible cell injury and necrosis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been established that hepatocellular glycogen level is a potentially important and manageable factor in maintaining hepatocellular integrity and function by generating ATP [27][28][29]. Once glycogen is consumed, ATP depletion rapidly develops, leading to a series of events that eventually cause irreversible cell injury and necrosis [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…6,36,37 Interestingly, early recent work with rats with Dgalactosamine-induced fulminant liver failure showed that exogenous ATP did not improve survival, and at high doses it was detrimental to survival. 38 POTENTIAL TREATMENTS FOR ALF Now that the different modes of cell death in ALF have been well characterized, the opportunity arises to interrupt these pathways in the treatment for ALF. Several caspase inhibitors have shown promising responses by improving survival in mice following induction of ALF 39,40 ; however, perhaps because of the broad effects of these medications and the significant risk of mortality in the target population, these inhibitors have yet to be tested in humans with ALF.…”
Section: Necroapoptosismentioning
confidence: 99%